An Empirical Study on Consumer Behavior of Life Insurance Purchasing Decision - Ashish Kumar Srivastava (The Creative Launcher, 2020)
The Indian economy is one of the fastest growing economies in the world with GDP per capita growing at a rate of 7.1% per annum1. The country is also experiencing a demographic shift towards a younger population with about 35% of the population being between 15 and 34 years of age2 in 2017. In the next few decades, unprecedented numbers of young people are expected to enter the workforce, earn and save part of their earnings. India’s household financial savings were estimated to be about 8.1% of the Gross National Disposable Income (GNDI), or about $26 trillion in the financial year 2016-17. About a fourth of these savings are invested in insurance3. Thus, the insurance sector is large and will grow further in the coming years. Understanding consumer behavior and what influences purchase decisions is important for different players in this industry including regulators and insurance companies. Despite recent growth, the life insurance market in India has low penetration rates compared to many other countries. Financial inclusion is one of the primary concerns of policy makers across the world. Now the author has described several aspects about consumer behavior about Life Insurance at the event on purchasing.